THE EFFECT OF FINANCIAL DISTRESS, BOOK TAX DIFFERENCE AND GROWTH OPPORTUNITY ON ACCOUNTING PRUDENCE WITH LITIGATION RISK AS A MODERATOR - Putri Puspa Safitri; Hesty Erviani Zulaecha (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This study analyzes the effect of financial distress, book-tax difference, and growth opportunity on accounting prudence, with litigation risk as a moderating variable. The study subjects were state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. The sampling technique used was purposive sampling. Based on the established research criteria, eight companies were selected. The data used were secondary data obtained from the Indonesia Stock Exchange (IDX) website. The analytical method used was panel data regression analysis. The results show that financial distress and book-tax difference have a significant positive effect on accounting prudence, while growth opportunity has a significant negative effect. Litigation risk strengthens the relationship between financial distress and accounting prudence, but weakens the relationship with book-tax difference and growth opportunity. This study contributes to the accounting prudence literature by highlighting the moderating role of litigation risk and the practical implications for SOE management and regulators in improving the quality of financial reporting and risk management. This study uses EViews 12.0.